The Measurement and development of empathy in nursing - Reynolds, William J (Ashgate, 2000)
Empathy is known to be crucial to helping relationships, but professional helpers, including nurses, do not normally display much empathy as it has not been measured in clients\' terms and accordingly taught. This text examines a study in which a client-centred empathy scale was developed - the client-centred measure of empathy was found to be reliable and valid and a course designed to teach nurses to offer empathy in clients\' terms was effective. The findings of the study have implications for the future design of nurse eduction and the goals of the health service.
Developments in nursing and health care
Keywords: Nursing; empatie; ošetřovatelství; Empathy; Patients; pacienti